Chondroid Chordoma and Nasal Adenocarcinoma: An Exceptional Association. (17th September 2012) - Gallet, Patrice; Marcon, Nathalie; Georgel, Thomas; Vignaud, Jean-Marie; Parietti-Winkler, Cécile; Jankowski, Roger
Abstract : Collision tumors are exceptional, associating two independent tumoral contingents. We report a case of an association of two rare tumors: sinonasal adenocarcinoma and chondroid chordoma. Initially, only adenocarcinoma was diagnosed. The treatment consisted of endoscopic endonasal surgery followed by conventional radiotherapy. After 18 months, a local recurrence was diagnosed after a facial trauma, but the true histology was difficult to assess. The tumor was dual, associating adenocarcinoma and chondroid chordoma, with atypical localization in the ethmoid. Further evolution was particularly aggressive. We discuss the key points of this observation.